Effect of microencapsulation with the Maillard reaction products of whey proteins and isomaltooligosaccharide on the survival rate of Lactobacillus rhamnosus in white brined cheese. (September 2017) - Liu, Lu; Chen, Ping; Zhao, Weili; Li, Xiaodong; Wang, Haixia; Qu, Xiuwei
Abstract: The objective of this study was to investigate the effect of microencapsulation using the Maillard reaction products of whey proteins and isomaltooligosaccharides on the viability of Lactobacillus rhamnosus ( L. rhamnosus ) during the storage of cheese as well as upon exposure to simulated gastrointestinal condition. The results demonstrated that the number of viable Lactobacillus rhamnosus was reduced significantly ( P  <  0.05 ) from day 28 to day 90 of the storage period of white brined cheeses, but reduction of L. rhamnosus in the cheese containing free bacteria (approximately 4 log) was significantly ( P  <  0.05 ) higher than in the cheese containing microencapsulated bacteria (approximately 1 log). Under conditions that simulated the gastrointestinal tract, the number of microencapsulated Lactobacillus rhamnosus in cheese was more than 7.3 log cfu g −1 higher than the minimum therapeutic level. The results showed that microencapsulation of Lactobacillus rhamnosus using the Maillard reaction products of whey proteins and isomaltooligosaccharides was effective in protecting the bacteria in white brined cheese, and the sensory properties of the cheeses were not affected by the addition of microencapsulated probiotic bacteria. Highlights: The microencapsulation could increase the survival rate of probiotic in cheese during the storage. The microencapsulation provided better protection of probiotic in simulated gastrointestinal conditions. The sensory properties of cheeses was not affected by the addition of microencapsulated probiotic.